Organize and mobilize for implementation effectiveness to improve overdose education and naloxone distribution from syringe services programs: a randomized controlled trial - Lambdin, Barrot H.; Bluthenthal, Ricky N.; Garner, Bryan R.; Wenger, Lynn D.; Browne, Erica N.; Morris, Terry; Ongais, Lee; Megerian, Cariné E.; Kral, Alex H. (Implementation science : IS, 2024)
Background The United States (US) continues to face decades-long increases in opioid overdose fatalities. As an opioid overdose reversal medication, naloxone can dramatically reduce opioid overdose mortality rates when distributed to people likely to experience or witness an opioid overdose and packaged with education on its use, known as overdose education and naloxone distribution (OEND). Syringe services programs (SSPs) are ideal venues for OEND with staff who are culturally competent in providing services for people who are at risk of experiencing or observing an opioid overdose. We carried out a randomized controlled trial of SSPs to understand the effectiveness of the organize and mobilize for implementation effectiveness (OMIE) approach at improving OEND implementation effectiveness within SSPs. Methods Using simple randomization, 105 SSPs were enrolled into the trial and assigned to one of two study arms — (1) dissemination of OEND best practice recommendations (Control SSPs) or the OMIE approach along with dissemination of the OEND best practice recommendations (i.e., OMIE SSPs). OMIE SSPs could participate in 60-min OMIE sessions once a month for up to 12 months. At 12-month post-baseline, 102 of 105 SSPs (97%) responded to the follow-up survey. Results The median number of sessions completed by OMIE SSPs was 10. Comparing OMIE SSPs to control SSPs, we observed significant increases in the number of participants receiving naloxone (incidence rate ratio: 2.15; 95% CI : 1.42, 3.25; p < 0.01) and the rate of naloxone doses distributed per SSP participant (adjusted incidence rate ratio: 1.97; 95% CI : 1.18, 3.30; p = 0.01). We observed no statistically significant difference in the number of adopted best practices between conditions (difference in means 0.2, 95% CI : − 0.7, 1.0; p = 0.68). We also observed a threshold effect where SSPs receiving a higher OMIE dose had greater effect sizes with regard to the number of people given naloxone and the number of naloxone doses distributed. Conclusions In conclusion, the multifaceted OMIE approach was effective at increasing naloxone distribution from SSPs, despite substantial external shocks during the trial. These findings have major implications for addressing the overdose crisis, which has continued unabated for decades. Trial registration ClinicalTrials.gov, NCT03924505 . Registered 19 April 2019.